Corrigendum to “Pathways to conventional and radical climate action: The role of temporal orientation, environmental cognitive alternatives, and eco-anxiety” [Glob. Environ. Change 87 (2024) 102886] - Charlie R. Pittaway; Kelly S. Fielding; Winnifred R. Louis (Global Environmental Change, 2026)

Who do we trust on climate change, and why? - Sarah MacInnes; Matthew J. Hornsey; Christian Bretter; Samuel Pearson; Kelly S. Fielding; David Bersoff (Global Environmental Change, 2026)

Evaluating environmental health communication: The readability of factsheets about per- and polyfluoroalkyl substances (PFAS) - Carla R. Magi-Prowse; Kelly S. Fielding; Kevin V. Thomas; Kylie Morphett (International Journal of Hygiene and Environmental Health, 2026)

Can Instagram contribute to the wellbeing and flourishing of Australian farming women in the midst of climate challenges? - Amy R. Samson; Kelly S. Fielding; Natalie Collie (Journal of Rural Studies, 2025)

Eliciting diverse perspectives to prioritize community actions for biodiversity conservation - Angela J. Dean; Kelly S. Fielding; Liam D. G. Smith; Emma K. Church; Kerrie A. Wilson (Conservation Biology, 2025)
Communities have a strong role in protecting biodiversity. In addition to participation in restoration, a range of actions in the public or private sphere may support biodiversity. Despite this, there is a lack of clarity about what actions should be prioritized for behavior change campaigns. We developed and applied a method to prioritize community actions for biodiversity conservation that incorporates an expert‐based assessment of impact and a community‐informed measure of the likelihood of uptake. In stage 1, experts ( n = 143) completed a survey that quantified the relative impact of actions based on best–worst scaling of perceived impact. In stage 2, surveyed community members ( n = 3200) ranked the likelihood of adopting actions based on the ease or difficulty of performing each action, and the opportunity for change based on the proportion of respondents not yet engaging in each behavior. Experts gave the following actions the highest ranking for impact: voting for the environment (first), participating in restoration in ecological priority areas (second), and purchasing and protecting remnant bushland (third). When considering the disciplinary background and institutional background of experts, voting and participating in restoration activities remained in the upper ranked options. However, there was some divergence between these groups. For example, reducing beef consumption was ranked third by university‐based experts but ranked 28th by experts based in state government. Overall, community members ranked the following behaviors as most likely to be adopted: following quarantine laws (first), reducing plastic use (second), and managing pets (third). Top likelihood ranking of actions was minimally affected by community characteristics (nature relatedness, gender, location). Integrating these findings, the action ranked most favorably for impact, likelihood, and opportunity was participating in restoration. Choosing actions for behavior change campaigns requires consideration of the entire social–ecological system—from social factors that enable or constrain adoption to the ecological impact of actions across relevant social and ecological contexts.

Landholders’ intentions to engage in private land conservation agreements under climate risk - Nanda Kaji Budhathoki; Kelly S. Fielding; Jonathan R. Rhodes; Carla L. Archibald; Daniel Lunney; James Brazil-Boast; Scott Benitez Hetherington; James A. Fitzsimons; Md Sayed Iftekhar (Journal of Environmental Management, 2025)

Media ownership and coverage patterns of established, disruptive, and unconventional climate advocacy groups - Robyn E. Gulliver; Xiongzhi Wang; Winnifred R. Louis; Kelly S. Fielding; Rebecca M. Colvin (Climatic Change, 2025)
Groups advocating on climate and environmental issues often seek to obtain media coverage to increase public awareness of their cause, yet comparatively little is understood about the factors influencing the volume and content of that coverage. This study investigates the quantity and characteristics of media coverage of climate advocacy groups through a mixed-method analysis of 17,380 Australian media articles published between 2017–2022. Four types of advocacy groups were the focus: ‘Established’ groups (large professionalised environmental groups); ‘Disruptive’ groups (the greatest use of civil resistance tactics); and two types of what we call ‘Unconventional advocates’ – those who advocate for action on climate change but from a social identity position that is either typically not associated with climate action (‘Role-based unconventional advocates’, such as parents or doctors) or has a history of conflict with climate or other environmental causes and environmentalists (‘Conflict-spanning unconventional advocates’, such as farmers and political conservatives). Findings indicate that linguistic cues associated with conflict, achievement, and emotional sentiment differed significantly according to the advocacy group type and media ownership. While Established groups gained the greatest volume of coverage, Disruptive groups attracted the highest conflict language and lowest achievement language, particularly in outlets published by News Corp (the Murdoch owned media company). Meanwhile, conflict-spanning unconventional advocates received coverage using language with the lowest levels of conflict and highest levels of achievement. Our findings highlight the potential for new types of climate advocates to gain comparative sympathetic media coverage and potentially expand the social basis of support for climate action.

Is Australia's urban-regional schism on climate reality or rhetoric? - R.M. Colvin; Frank Jotzo; Kelly S. Fielding (Journal of Rural Studies, 2024)

Pathways to conventional and radical climate action: The role of temporal orientation, environmental cognitive alternatives, and eco-anxiety - Charlie R. Pittaway; Kelly S. Fielding; Winnifred R. Louis (Global Environmental Change, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Capturing free-roaming dogs for sterilisation: A multi-site study in Goa, India - H.R. Fielding; K.A. Fernandes; V.R. Amulya; D. Belgayer; A. Misquita; R. Kenny; A.D. Gibson; L. Gamble; B.M.de C. Bronsvoort; R.J. Mellanby; S. Mazeri (Preventive Veterinary Medicine, 2023)

The road towards effective governance and management of marine protected areas in South Africa: evolving policies, paradigms and processes - SP Kirkman; P Kowalski; BQ Mann; GM Branch; MG van der Bank; KJ Sink; P Fielding; JB Mann-Lang; MC Pfaff; D Kotsedi; R Adams; S Dlulisa; et al. (African Journal of Marine Science, 2023)

In situ calcite U–Pb geochronology of carbonate and clastic sedimentary rocks from the Canning Basin, Western Australia - Z. Li; K. Rankenburg; L. S. Normore; N. J. Evans; B. I. A. McInnes; L. M. Dent; I. O. H. Fielding (Australian Journal of Earth Sciences, 2023)

Estimated Erosion from Clearcut Timber Harvests in the Southeastern United States - Jonah A H Fielding; Brent S Hawks; W Michael Aust; M Chad Bolding; Scott M Barrett (Forest Science, 2022)
Timber harvests with inadequate forestry best management practices (BMPs) can accelerate soil erosion, which has been associated with reductions in water quality and site productivity. Previous studies affirm positive water quality effects accrued by harvesting with BMPs. However, few studies document erosion rates and masses associated with harvest and access network features (e.g., decks, roads, skid trails, stream crossings) across different southeastern regions. This research evaluated 109 recent harvests across eleven southeastern states and three topographically different regions (Coastal Plain, Piedmont, and Mountains). Descriptive statistics of erosion for harvests and access features were developed from USLE-Forest model estimates. Harvests and access network areas were used in conjunction with erosion averages to calculate total erosion masses. Across the southeast, combined network features averaged nearly 12% of total harvest area yet produced approximately 48% of total site erosion due to disproportionately higher erosion rates. Regional differences indicated that the Mountain region had an average overall erosion rate of 6.8 t/ac/yr, whereas the Piedmont and Coastal Plain sites had lower average erosion rates of 2.7 and 2.2 t/ac/yr, respectively. Results suggest that additional BMP implementation strategies may be beneficial for erosion control from roads, skid trails, and stream crossings, particularly in erosive landscapes.

Estimating the average distribution of Antarctic krill Euphausia superba at the northern Antarctic Peninsula during austral summer and winter - V. Warwick-Evans; S. Fielding; C. S. Reiss; G. M. Watters; P. N. Trathan (Polar Biology, 2022)
This study was performed to aid the management of the fishery for Antarctic krill Euphausia superba . Krill are an important component of the Antarctic marine ecosystem, providing a key food source for many marine predators. Additionally, krill are the target of the largest commercial fishery in the Southern Ocean, for which annual catches have been increasing and concentrating in recent years. The krill fishery is managed by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR), which has endorsed a new management framework that requires information about the spatial distribution and biomass of krill. Here, we use krill density estimates from acoustic surveys and a GAMM framework to model habitat properties associated with high krill biomass during summer and winter in the northern Antarctic Peninsula region, an area important to the commercial fishery. Our models show elevated krill density associated with the shelf break, increased sea surface temperature, moderate chlorophyll-a concentration and increased salinity. During winter, our models show associations with shallow waters (< 1500 m) with low sea-ice concentration, medium sea-level anomaly and medium current speed. Our models predict temporal averages of the distribution and density of krill, which can be used to aid CCAMLR’s revised ecosystem approach to fisheries management. Our models have the potential to help in the spatial and temporal design of future acoustic surveys that would preclude the need for modelled extrapolations. We highlight that the ecosystem approach to fisheries management of krill critically depends upon such field observations at relevant spatial and temporal scales.

The relationship between country and individual household wealth and climate change concern: the mediating role of control - Céline Nauges; Sarah Ann Wheeler; Kelly S. Fielding (Environment, Development and Sustainability, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Dating hypogene iron mineralization events in Archean BIF at Weld Range, Western Australia: insights into the tectonomagmatic history of the northern margin of the Yilgarn Craton - Paul Duuring; João O. S. Santos; Imogen O. H. Fielding; Timothy J. Ivanic; Steffen G. Hagemann; Thomas Angerer; Yong-Jun Lu; Malcolm Roberts; Jinwoo Choi (Mineralium Deposita, 2020)

Will COVID-19 change the way we teach medical physics post pandemic? - A. Haworth; A. L. Fielding; S. Marsh; P. Rowshanfarzad; A. Santos; P. Metcalfe; R. Franich (Physical and Engineering Sciences in Medicine, 2020)

Using ingroup messengers and ingroup values to promote climate change policy - Kelly S. Fielding; Matthew J. Hornsey; Ha Anh Thai; Li Li Toh (Climatic Change, 2020)

Coupled, Physics-Based Modeling Reveals Earthquake Displacements are Critical to the 2018 Palu, Sulawesi Tsunami - T. Ulrich; S. Vater; E. H. Madden; J. Behrens; Y. van Dinther; I. van Zelst; E. J. Fielding; C. Liang; A.-A. Gabriel (Pure and Applied Geophysics, 2019)

From intrabasinal volcanism to far-field tectonics: causes of abrupt shifts in sediment provenance in the Devonian–Carboniferous Drummond Basin, Queensland - K. Sobczak; S. E. Bryan; C. R. Fielding; M. Corkeron (Australian Journal of Earth Sciences, 2019)

Probabilistic flood risk analysis considering morphological dynamics and dike failure - J. Oliver; X. S. Qin; O. Larsen; M. Meadows; M. Fielding (Natural Hazards, 2018)

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Comparing Public Perceptions of Alternative Water Sources for Potable Use: The Case of Rainwater, Stormwater, Desalinated Water, and Recycled Water - Kelly S. Fielding; John Gardner; Zoe Leviston; Jennifer Price (Water Resources Management, 2015)

Human cytomegalovirus: taking the strain - Gavin W. G. Wilkinson; Andrew J. Davison; Peter Tomasec; Ceri A. Fielding; Rebecca Aicheler; Isa Murrell; Sepher Seirafian; Edward C. Y. Wang; Michael Weekes; Paul J. Lehner; Gavin S. Wilkie; Richard J. Stanton (Medical Microbiology and Immunology, 2015)

Recent changes in the snout position and surface velocity of Gangotri glacier observed from space - Puneet Saraswat; Tajdarul H. Syed; James S. Famiglietti; Eric J. Fielding; Robert Crippen; Nishant Gupta (International Journal of Remote Sensing, 2013)

Identification of serum analytes and metabolites associated with aerobic capacity - Michael S. Lustgarten; Lori Lyn Price; Tanya Logvinenko; Christos Hatzis; Nandan Padukone; Nicholas V. Reo; Edward M. Phillips; Dylan Kirn; John Mills; Roger A. Fielding (European Journal of Applied Physiology, 2013)

Muscle power failure in mobility-limited older adults: preserved single fiber function despite lower whole muscle size, quality and rate of neuromuscular activation - Kieran F. Reid; Gheorghe Doros; David J. Clark; Carolynn Patten; Robert J. Carabello; Gregory J. Cloutier; Edward M. Phillips; Lisa S. Krivickas; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2012)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

A transposon insertion single-gene knockout library and new ordered cosmid library for the model organism Streptomyces coelicolor A3(2) - L. T. Fernández-Martínez; R. Del Sol; M. C. Evans; S. Fielding; P. R. Herron; G. Chandra; P. J. Dyson (Antonie van Leeuwenhoek, 2011)

Multi-step immunofluorescent analysis of vitamin D receptor loci and myosin heavy chain isoforms in human skeletal muscle - Lisa Ceglia; Mauricio da Silva Morais; Lara K. Park; Evan Morris; Susan S. Harris; Heike A. Bischoff-Ferrari; Roger A. Fielding; Bess Dawson-Hughes (Journal of Molecular Histology, 2010)

Assessing the applicability of Emiliania huxleyi coccolith morphology as a sea‐surface salinity proxy - Samuel R. Fielding; Jens O. Herrle; Jórg Bollmann; Richard H. Worden; David J. S. Montagnesd (Limnology and Oceanography, 2009)
Culture experiments were used to assess the applicability of Emiliania huxleyi coccolith morphology as a palaeo‐sea‐surface salinity (SSS) proxy. Coccolith morphology was dependent on salinity over a range reflecting present day marine conditions; both coccolith size and the number of coccolith elements increased linearly with increasing salinity. Using regression analysis, the effect of salinity on coccolith morphology was compared to those previously observed in sediment core‐top and plankton data. No significant differences were found between the slopes of these data, suggesting that salinity is the primary control on E. huxleyi coccolith size and element number in the ocean. However, the intercepts of the culture data were significantly higher. A combination of experimental and literature analysis indicated that temperature and nutrients were unlikely to be the causes of this discrepancy. Literature analysis also highlighted that coccolith size data from marginal environments displayed different intercepts to those from the open‐ocean data. This suggests that discrete morphotypes exist in these marginal locations. We, therefore, recommend that the original E. huxleyi coccolith morphology palaeo‐SSS transfer function requires further evaluation before being routinely applied.

Distribution, growth, diet and foraging behaviour of the yellow‐fin notothen Patagonotothen guntheri (Norman) on the Shag Rocks shelf (Southern Ocean) - M. A. Collins; R. S. Shreeve; S. Fielding; M. H. Thurston (Journal of Fish Biology, 2008)
The distribution, total length ( L T ) frequency and diet of Patagonotothen guntheri are described from 14 bottom trawl surveys conducted on the Shag Rocks and South Georgia shelves in the austral summers from 1986 to 2006. Patagonotothen guntheri (80–265 mm L T ) were caught on the Shag Rocks shelf from depths of 111 to 470 m, but no specimens were caught on the South Georgia shelf. Multiple cohorts were present during each survey and L T ‐frequency analysis of these cohorts suggests that growth was slow (von Bertalanffy K = 0·133). Evidence from stomach contents and acoustic data (2005 and 2006) showed that P. guntheri is primarily a pelagic feeder, migrating from the sea floor towards the surface to feed during daylight. The diet of smaller fish ( Rhincalanus gigas , whilst larger fish principally consumed the pelagic hyperiid amphipod, Themisto gaudichaudii and Antarctic krill Euphausia superba . Some larger fish also took benthic prey.

Severe retinitis pigmentosa mapped to 4p15 and associated with a novel mutation in the PROM1 gene - Qingjiong Zhang; Fareeha Zulfiqar; Xueshan Xiao; S. Amer Riazuddin; Zahoor Ahmad; Raphael Caruso; Ian MacDonald; Paul Sieving; Sheikh Riazuddin; J. Fielding Hejtmancik (Human Genetics, 2007)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Severe autosomal recessive retinitis pigmentosa maps to chromosome 1p13.3–p21.2 between D1S2896 and D1S457 but outside ABCA4 - Qingjiong Zhang; Fareeha Zulfiqar; Xueshan Xiao; S. Amer Riazuddin; Radha Ayyagari; Farooq Sabar; Raphael Caruso; Paul A. Sieving; Sheikh Riazuddin; J. Fielding Hejtmancik (Human Genetics, 2005)

Variants of the CD40 ligand gene are not associated with increased susceptibility to tuberculosis in West Africa - Sarah J. Campbell; Pardis Sabeti; Katherine Fielding; Jackson Sillah; Boubacar Bah; Per Gustafson; Kebba Manneh; Ida Lisse; Giorgio Sirugo; Richard Bellamy; Steve Bennett; Peter Aaby; et al. (Immunogenetics, 2003)

A 5-base insertion in the γC-crystallin gene is associated with autosomal dominant variable zonular pulverulent cataract - Zhaoxia Ren; Anren Li; Barker S. Shastry; Tirunilai Padma; Radha Ayyagari; Mark H. Scott; Marshall M. Parks; Muriel I. Kaiser-Kupfer; J. Fielding Hejtmancik (Human Genetics, 2000)

A 5-base insertion in the γC-crystallin gene is associated with autosomal dominant variable zonular pulverulent cataract - Zhaoxia Ren; Anren Li; Barker S. Shastry; Tirunilai Padma; Radha Ayyagari; Mark H. Scott; Marshall M. Parks; Muriel I. Kaiser-Kupfer; J. Fielding Hejtmancik (Human Genetics, 2000)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)